Altitudinal Distribution of Bryoflora at Chandragiri Mountain Forest of Kathmandu District, Central Nepal (Journal of Natural History Museum, 2015)
Chandragiri Mountain forest in Kathmandu borders Makwanpur district to the west was least known for bryophytes till this study was conducted. This mountain forest with varying elevation ranges from 1365 to 2300 m offered different habitat types for diverse bryofloral species which included 58 species of 39 genera categorized under 27 families and nine orders. Of the recorded species 18 species were rare and five new records to country’s list. Sauteria spongiosa (Kashyap) S. Hatt., a rare moss species was not recorded in this study though was reported for the fi rst time at 2250 m of this mountain in 1982. The habitat of this moss has completely been destroyed now due to expansion of the road in this part.J. Nat. Hist. Mus. Vol. 28, 2014: 81-92